PENGARUH FAKTOR FINANSIAL DAN NON FINANSIAL TERHADAP NILAI PERUSAHAAN SUB SEKTOR PULP DAN KERTAS - Triana Anggraini; Endah Sri Wahyuni (Universitas Budi Luhur, 2022)
This Study aims to examine financial an non-financial factors on firm value in the pulp and paper listed on the Indonesia Stock Exchange. The financial factorsis seen from liquidity and profitability, while non- financial is seen from the board of directors and independent commissioners, firm value is measured using Tobin’s Q. The population uses the pulp nad paper sub sector for the period 2013 -2020 with sampling using purposive sampling technique, there are 7 companies that are sampled. The method used multiple linear regression with SPSS software. Based on the test result, shown that independent commissioners, liquidity, and profitability have a significant effect on firm value, while the board of directors has no effect on firm value.